Majoritarian Religion, Cultural Justification and Nonreligion: Finland in the International Context - Taira, Teemu; Beaman, Lori (Temenos - Nordic Journal for the Study of Religion, 2022)
This article considers the turn to culture and heritage as a strategy for the preservation of majoritarian religious practices, including the implications of such a strategy for nonreligious people. This turn has been observed in analyses of court cases in which religious or cultural nature of symbols and practices has been negotiated. Drawing from previous scholarship regarding the turn, this article pays special attention to Finland by examining if and how cultural justification of symbols and practices takes place. We suggest that the shift to culture applies to Finland, although in international comparison Finnish instances are more prominent in public (media) discourses that refer to laws and legal experts than in court cases. We also argue that one of the consequences of this international development is that it becomes increasingly difficult for nonreligious people and also members of religious minorities to feel part of ‘us’ in a situation where justification by referring to ‘our culture and heritage’ is one of the strategies to define who and what belongs to ‘us’.